Relationship between Psychological Flexibility & Burnout among Research Student - Anosha Nazir (PJE, 2024)
The study investigates the relationship between psychological flexibility and burnout among MPhil research students in Islamabad and Rawalpindi universities. Data from both genders (n = 166 males, n = 134 females) was collected using purposive sampling technique. Psychological Flexibility Scale for University Students and Maslach Burnout Inventory Student Survey measured study variables. Results indicate a negative correlation between psychological flexibility and burnout, with competence positively correlated with psychological flexibility, while exhaustion and cynicism were negatively correlated. Gender differences emerged, with males scoring higher on psychological flexibility and females on burnout. Age showed no significant differences, but married participants scored higher on burnout, while unmarried scored higher on psychological flexibility. Employed students had higher burnout, while unemployed scored higher on psychological flexibility. Nuclear family background correlated with higher psychological flexibility and exhaustion. Social science students scored higher on psychological flexibility and competence. Supervisor’s support correlated with increased psychological flexibility, competence, and decreased exhaustion and cynicism, enhancing research students' overall well-being.